Implementation of STEAM-Based Project Learning Model to Improve Elementary Student’s Learning Outcomes - Rostikawati, Teti; Budiana, Sandi; Karmila, Nita; Saptiani, Bintang Indah; Sari, Nurmala (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
This research aims to determine how the implementation of the Science, Technology, Engineering, Art, and Mathematics-Based Project-Based Learning Model affects the learning outcomes of students in the sub-theme of project-based activities and literacy. The research method used was a quasi-experimental two-group design at Bondongan Public Elementary School in Bogor City. The subjects of this study consist of 63 students of fifth grade. This research was conducted in the first semester of the academic year. The results of the study showed that the implementation of the STEAM-based project-based learning model had an effect on student learning outcomes in the sub-theme of project-based activities and literacy. This is evident from the N-Gain score in the experimental group of 69, while the control group obtained an N-Gain score of 39. The hypothesis testing results state that H0 is rejected and Ha is accepted because t-count (14.56) is greater than t-table (1.9996). Thus, it can be concluded that the implementation of the STEAM-based Project-Based Learning Model effectively improves student learning outcomes in the sub-theme of project-based activities and literacy. It is hoped that the results of this study can provide new knowledge about how the implementation of innovative learning models can improve the learning outcomes of students in elementary school.